Early prenatal investigation of a pregnancy at risk of adenosine deaminase deficiency using chorionic villi. Issue 1 (February 1986) - Aitken, D A; Gilmore, D H; Frew, C A; Ferguson-Smith, M E; Carty, M J; Chatfield, W R
Abstract : A pregnancy at risk for adenosine deaminase deficiency and severe combined immunodeficiency disease was investigated using samples of chorionic villi obtained during the eighth week of pregnancy. Adenosine deaminase levels suggested that the fetus was a probable carrier and that a diagnosis of severe combined immunodeficiency disease could be excluded. Enzyme and chromosome results were available within 24 hours of the chorionic villous sampling procedure, and were confirmed on amniotic fluid cell cultures after amniocentesis at 17 weeks' gestation and on cord blood at delivery.